Pressure-induced superconductivity and quantum phase transitions in the Rashba material BiTeCl. (May 2019) - Jin, M.L.; Zhang, S.J.; Xing, L.Y.; Li, W.M.; Zhao, G.Q.; Wang, X.C.; Long, Y.W.; Li, X.D.; Bai, H.Y.; Gu, C.Z.; Jin, C.Q.
Abstract: Recent theoretical predictions have indicated that BiTeX (X = Cl, Br, I) type strong spin orbital coupling semiconductor compounds with strong Rashba effects are suitable for use as topological insulators under compressed conditions and novel phenomena have been identified in experiments. The compound BiTeCl is expected to exhibit a topological nontrivial state under pressure. In this study, we obtained measurements based on the resistivity, Hall coefficient, synchrotron X-ray diffraction, and Raman spectroscopy using the Rashba semiconductor BiTeCl crystal at high pressures up to 54.8 GPa. Our experiments indicated that the Rashba semiconductor BiTeCl exhibited a pressure-induced metal to insulator-like transition at 2.8 GPa. A pressure-induced structural phase transition was observed above 5.5 GPa, which was followed by a superconducting transition. The superconducting transition temperature ( T C ) increased to a maximum 4.2 K with pressures up to 32 GPa. Compared with BiTeI, the structural phase transition of BiTeCl occurs at a relatively lower pressure due to the weaker Rashba effects, where the inner chemical pressure is affected by the replacement of I with Cl.